Information technology and Baumol's cost disease in healthcare services: a research agenda. (18th June 2020) - Mithas, Sunil; Hofacker, Charles F.; Bilgihan, Anil; Dogru, Tarik; Bogicevic, Vanja; Sharma, Ajit
Abstract : Purpose: This paper advances a research agenda for service researchers at the intersection of healthcare and information technologies to improve access to quality healthcare at affordable prices. The article reviews key trends to provide an agenda for research focusing on strategies, governance and management of key service processes. Design/methodology/approach: This paper synthesizes literature in information systems, service management, marketing and healthcare operations to suggest a research agenda. The authors draw on frameworks such as the interpretive model of technology, technology acceptance model, assemblage theories and Baumol's cost disease to develop their arguments. Findings: The paper situates strategy-related service management questions that service providers and consumers face in the context of emerging healthcare and technology trends. It also derives implications for governance choices and questions related to that. Research limitations/implications: The paper discusses service management challenges and concludes with an agenda for future research that touches on governance and service management issues. Practical implications: This paper provides implications for healthcare service providers and policymakers to understand new trends in healthcare delivery, technologies and facilities management to meet evolving customer needs. Social implications: This paper provides implications for managing healthcare services that touch on many social and societal concerns. Originality/value: This conceptual paper provides background and review of the work at the intersections of information systems, marketing and healthcare operations to draw implications for future research.